Regulatory Implications of The Public Financial Management Framework in Indonesia - Tirton Nefianto; Ayu Larasati (CV. Publikasi Indonesia, 2024)
Public Financial Management a set of laws, rules, and standards is an important part of regulating the systems and processes used by each sovereign state and local government, to mobilize revenue, allocate public funds, conduct public spending, and budget audits. The purpose of public financial management itself is to increase efficiency and transparency in the use of public resources and eliminate the inefficiency of public resources. The regulatory framework for Public Financial Management can carry out analytical and critical practices in helping to facilitate services efficiently and effectively. This article uses a qualitative method with a descriptive approach to describe or analyze a research result but is not used to make a broader conclusion. Analysis and Discussion The Government of Indonesia is aware that there are regulations governing budgeting, although some of them do not understand and study these documents comprehensively. The regulatory framework governing fund management influences service delivery. In conclusion, the regulatory framework explains how public budgets are used to provide better services. The regulation is designed to help to reduce budget waste and prevent corruption.